Peran Pendidikan Sejarah Terhadap Nasionalisme dan Patriotisme Siswa SMA: Suatu SLR - Rio Refki Maulana; Zahra Maulidya Hanifah; Levina Naura Artianti; Aulia Miftahurriqi; Ilmi Solihat (Jurnal Artefak, 2025)
This study aims to map research trends and findings on the role of history education in fostering nationalism and patriotism among Indonesian high school students from 2015 to 2025. Using a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework, data were collected from Google Scholar, SINTA, Garuda databases. Out of 500 initial articles, 20 met the PICOC inclusion criteria and were analyzed through thematic synthesis. The findings reveal three main themes: digital technology integration in history learning, revitalization of local history to strengthen national identity, and participatory methods that foster empathy and historical awareness. History education plays a crucial role in internalizing national values in the digital era. This review is limited to high school-level studies and predominantly qualitative designs; thus, further mixed-method research is recommended to enhance result validity.